Effects of dietary lecithin and l-carnitine on fatty acid composition and lipid-metabolic genes expression in subcutaneous fat and longissimus thoracis of growing-finishing pigs. (February 2018) - Meng, Qingwei; Sun, Shishuai; Sun, Yuecheng; Li, Jianan; Wu, Di; Shan, Anshan; Shi, Baoming; Cheng, Baojing
Abstract: A 2 × 2 factorial experiment was conducted to investigate the effects of dietary lecithin andl -carnitine on fatty acid composition and lipid-metabolic genes expression in subcutaneous fat and longissimus thoracis of growing-finishing pigs. 160 barrows were assigned to 4 treatments consisting of 8 replicates with 5 pigs in each. The total PUFA, C18:2n-6 and C18:3n-3 in subcutaneous fat were increased by lecithin but the effect of lecithin was dependent ofl -carnitine where supplementation of lecithin together withl -carnitine decreased total PUFA, C18:2n-6 and C18:3n-3.l -Carnitine increased the intramuscular fat content when supplemented with lecithin but no effect was observed without lecithin supplementation.l -Carnitine increased the mRNA expression of CPT1A, HSL, FABP4 and CRAT ; and reduced the mRNA expression of FAS and ACCα in subcutaneous fat. Lecithin increased the mRNA expression of ACCα and ME1 in longissimus thoracis .l -Carnitine increased the mRNA expression of FAS in longissimus thoracis when supplemented with lecithin but no effect was observed without lecithin supplementation.